The Comparison between HumanLeukocyte Antigen System Incidence in Patients with Bladder Cancer and Normal Controls - Falahatkar, Siavash; Donyamali, Hadiseh; Joafshani, Mohammad Ali; Shahrokhi Damavand, Reza; Hoda, Saba; Esmaeili, Samaneh; Gholamjani Moghaddam, Keivan; Nikpour, Sara (Urology Journal, 2014)
Abstract Purpose: To determine the frequency of human leukocyte antigen (HLA)-B5 in patients with bladder cancer compared with normal population. Materials and Methods: In this cross sectional study, from November 2009 until November 2010, 35 patients with pathologic diagnosis of bladder cancer who referred to urology clinic of Razi Hospital were studied. Also, 130 healthy transplant donation volunteers who referred for HLA-typing to Guilan Blood Transfusion Organization, were selected. Inclusion criterion was pathologic diagnosis of bladder cancer regardless of stage and grade of tumor. Exclusion criteria were presence of other urologic diseases. The information of these cases was extracted from medical records, collected and analyzed. Results: HLA-B5 was positive in 34.3% of the patient group and in 39.2% of the controls. Statistical analysis showed no significant association between HLA-B5 and bladder cancer (P = .15). There were no significant differences between grade (P = .107) and relapse (P = .327) of bladder tumor with presence of HLA-B5. Conclusion: There was no significant association between HLA-B5 and bladder cancer. The grade and the relapse of tumor had no association with presence or absence of HLA-B5.